Analysis of marketing information sources among smallholder vegetable farmers. Issue 1 (2nd January 2020) - Sharma Pandit, Sagun; Kuwornu, John K.M.; Datta, Avishek; Yaseen, Muhammad; Anal, Anil Kumar
ABSTRACT: Marketing of agricultural products is as important as production of the products. Acquisition of marketing information on agricultural products is necessary because lack of, and/or asymmetric, information has the potential of creating an imbalance between product supply and demand leading to loss to marketing channel members, especially farmers. The study was carried out from May to June 2016 in the central region of Nepal to investigate access and usefulness of sources of marketing information among smallholder vegetable farmers. A total information score was used to compare sources of marketing information available to farmers in relation to frequency of contact and usefulness of marketing information. The key sources of marketing information for farmers were notice board services, extension agents, traders, other farmers, and agrochemical dealers. The types of information available and used by farmers are limited either by applicability or acceptance. There needs to be more transparency with respect to dissemination of information to farmers. More sources of marketing information should be readily available to farmers, and the farmers need to accept them as reliable.